Reagan, in his own hand the writings of Ronald Reagan that reveal his revolutionary vision for America - Reagan, Ronald 1911-2004 (Free Press, 2001)
Presents a collection of annotated documents that reveal how Ronald Reagan served as the intellectual architect of the 1980s prosperity and of the strategy that won the Cold War.
Keywords: Reagan, Ronald -- Political and social views; Reagan, Ronald -- 1911-2004; Geschichte 1975-1979; Politik; Politische Einstellung; Quelle; Sozialpolitik; USA; United States -- Politics and government -- 1981-1989